Communal coping in high-level sports teams: A mixed-method investigation - Mahot, K.; Péte, E.; Lienhart, N.; Doron, J. (Psychology of Sport and Exercise, 2026)
Communal coping, defined as collectively perceiving and addressing stressors as "our problem," plays a critical role in teams` ability to manage stressful situations. By using a mixed-method approach this study examined (1) the extent to which athletes share their appraisals of stressful match situations, (2) the degree to which they perceive coping strategies as collectively enacted, and (3) psychosocial and contextual factors that may facilitate or hinder these shared processes. Forty-nine elite athletes from four high-level sports teams (basketball, football, and ice hockey) participated in this study. Quantitative data were analyzed using descriptive statistics, whereas qualitative data from the focus groups were analyzed using thematic analysis. The quantitative results indicated variability in athletes' shared appraisals of stress intensity and revealed differential use of communal coping strategies across teams and situations. Focus groups provided in-depth qualitative insights into the factors that influenced these processes. The findings highlight that communal coping is a complex social phenomenon influenced by communication, leadership, emotional expression, and environmental contexts such as competition stakes and timing. This study underscores the necessity for mixed methods approaches in future communal coping research, especially in ecological settings, emphasizing both shared appraisal and communal action dimensions. Recommendations for future research include employing larger samples, evaluating both primary and secondary appraisals, and explicitly examining perceptions of stress ownership to enhance understanding of communal coping among sports teams.